2006
DOI: 10.1097/01.hjh.0000234119.63519.5a
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of lipid enhancement of α1-adrenoceptor pressor sensitivity in hypertension

Abstract: These findings suggest that in hypertensive patients, the primary mechanism for short-term alpha1-pressor hypersensitivity in response to hyperlipidemia is via the acute impairment of BRS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
12
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 37 publications
1
12
1
Order By: Relevance
“…In contrast to our finding of preserved cardiovagal BRS in the face of acute hyperlipidemia, two previous humans studies reported impairments using an identical infusion protocol (8,9). There are at least several differences between these previous studies and ours that may help to explain the discrepant findings.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…In contrast to our finding of preserved cardiovagal BRS in the face of acute hyperlipidemia, two previous humans studies reported impairments using an identical infusion protocol (8,9). There are at least several differences between these previous studies and ours that may help to explain the discrepant findings.…”
Section: Discussioncontrasting
confidence: 99%
“…Second, baroreflex dysfunction may contribute to increased sympathetic outflow at rest due to an impaired ability of the baroreflexes to tonically restrain sympathetic outflow. Although these previous studies (8,9) are important, they do not provide evidence that systematic changes in baroreflex function occurred since only the cardiac arm, and not the sympathetic arm of the baroreflex, was studied.…”
mentioning
confidence: 93%
See 1 more Smart Citation
“…Two studies have presented conflicting evidence regarding acute baroreflex resetting and reduced baroreflex sensitivity in response to 1-h lipid infusion [14,44]. Although our present study was not designed to assess baroreflex function, the concomitant increase in BP, HR and MSNA supports the concept of resetting of the arterial baroreflexes to defend higher pressures.…”
Section: Baroreflex Modulationsupporting
confidence: 70%
“…Cholylglycine is one of the components of bile acid, and bile acid can consume the fat. The increased cholylglycine resulted from the rise of fat, which could lead to the rapid arterial baroreceptor resetting, baroreflex sensitivity reduction, and increased blood pressure 19, 20. Cholylglycine reduction observed after the treatment of Ping Gan prescription suggested that abnormal fat metabolism may be involved in the pathway of hypertension.…”
Section: Resultsmentioning
confidence: 99%